A comprehensive model of intercultural communication for international students living in culturally diverse societies: evidence from China - Nadeem, Muhammad Umar; Zabrodskaja, Anastassia (Frontiers in Communication, 2023)
Intercultural communication (IC) and international students go side by side in this era of internationalisation of higher education. The key concepts of IC, namely intercultural effectiveness (ICE), intercultural competence (ICC), intercultural adjustment (ICA), and intercultural adaptation (ICN) are used interchangeably in the literature. However, the present study argues that the stated concepts are theoretically different and further proposes that ICE, ICC, ICA, and ICN are phases of IC. Based on these conceptual differences, a comprehensive model of IC (CMIC) is proposed in this study. The CMIC explains that these four concepts are principally developmental phases for international students to become interculturally effective in adapting to a new culture. The current research further offers preliminary testing of CMIC, which is applied to international students in Shanghai, China through quantitative research followed by a survey. Instruments developed by experts were used in this study. International students were approached to participate in the survey at the convenience of the researcher. One hundred and seventy-one international students represented 18 different cultures, which reconfirms the culture-general approach by considering the stance of more than two different cultures. The findings revealed that international students became interculturally effective and competent which further enabled them to adjust to China. Later, their adjustment helped them adapt better to the new culture. The findings of this study validated the core predictions of the CMIC. As this is the first testing of CMIC on a relatively small sample, more extensive testing is expected soon to validate its assumptions in different contexts, such as Pakistan, Malaysia, and Australia, among others. The CMIC also suggests practical implications for policymakers and institutes of host countries regarding international students and other people living in a culturally different society.